Desempeño de los biodigestores con filtros de lechos plástico bacterianos en el tratamiento del agua residual doméstica de una vivienda unifamiliar - Chávez Garcés, Elvis Cicerón (2021)
In Ecuador, rural areas experience problems related to basic services, in this case the problem of sewerage service is addressed, which is supplied with the construction of septic tanks, which serve as a means of evacuating sewage, without However, these tend to become saturated, causing leaks of both odors and water to the surface causing health and environmental effects, since these leaks contaminate the soil and the nearest bodies of fresh water, which is why, The biodigester is proposed as a sustainable alternative for wastewater treatment, since it converts solid waste into natural gas or organic fertilizer, according to the user's need, however, this study focuses on its treatment capacity of sewage, which is why it was established that the general objective is "To determine the efficiency of the biodigester by implementing filt rivers of bacterial plastic beds through the monitoring and evaluation of wastewater, based on physical, chemical and bacteriological parameters, to mitigate the environmental pollution caused by these waters ”. For the development of the study, the experimental method was used through which, a water sample was taken, before and after the implementation of plastic beds, with which it is obtained that this system is efficient in terms of reduction of the pollutant load of the water treated with the biodigester...........